Analisis Pemahaman Konsep Fisika Peserta Didik dengan Instrumen Four-Tier Diagnotict Test - Sufiani, Yuni; Erniwati, Erniwati; Eso, Rosliana (Jurnal Penelitian Pendidikan Fisika, 2019)
This study aims to determine the understanding of the concept of students on mechanical wave material for students in class XI SMAN 1 Mawasangka Tengah. This type of research is a type of quantitative descriptive research. In this study, the authors wanted to analyze the students' conceptual understanding using the Four-tier diagnostic test instrument. The object of this research is the students of class XI IPA (1) and XI IPA (2) at SMAN 1 Mawasangka Tengah. The data in this study are primary data collected using four-tier diagnostic tests and documentation. The results of the data analysis showed that the average value of the percentage level of understanding of sub-concept students (1) the factors that influence the speed of the wave propagation, namely 4.4% understanding the concept, 81.4% misconception and 14.2% not understanding the concept (2) The current wave period is 23.5% understanding the concept, 64.4% misconception and 13.1% not understanding the concept (3) The frequency of the traveling wave is 32.2% understanding the concept, 51.4% misconception and 16.4 % do not understand the concept (4) Frequency on stationary waves is 36.6% understand the concept, 48.6% misconception and 14.7% do not understand the concept and (5) Wavelength on stationary waves is 15.8% understand the concept, 69 , 9% had misconceptions and 14.2% did not understand the concept. Based on the results of the analysis, it was concluded that: 1) The students' understanding of the concept of mechanical waves was included in the low category. Students who understood the concept were 22.5%, most of the students' understanding of the criteria did not understand the concept of 14.7% and 62.8% indicated that they had misconceptions. 2) Misconception of the high category found in the concept of factors that affect the speed of wave propagation by 81.4%.